Brand equity of the Private Higher Education Institutions accredited in high quality - Parra Garcia, Paula Milena; Ortegon Cortazar, Leonardo (RAN - Revista Academia & Negocios, 2023)
Purpose: To explore the Brand equity of Private Higher Education Institutions (PHEI) with high quality institutional accreditation in order to provide information on the key components of university management from a marketing perspective. Design/Methodology: A cross-sectional quantitative method was used to analyze the answers of survey applied to 402 students from 11 different on PHEI. The design is descriptive and correlational with factorial analysis of data. Results: The factorial solution suggests that PHEI brand equity is composed of brand image and perceived quality. Practical implications: It contributes to the multifaceted understanding of brand equity in the educational sector, discussing how to maintain brand positioning or awareness; furthermore, identifying opportunities for improvement to university brand communication and visibility. Originality/value: This research proves latent dimensions of brand equity applied to PHEI in Colombia, contributing to the body of knowledge on brand building strategies of PHEI in a marketing context.